The theory of screws : a study in the dynamics of a rigid body - Ball, Robert Stawell ([Place of publication not identifed] : [publisher not identified], 1876)
This is a reproduction of a classic text optimised for kindle devices. We have endeavoured to create this version as close to the original artefact as possible. Although occasionally there may be certain imperfections with these old texts, we believe they deserve to be made available for future generations to enjoy.
Introduction -- Chapter I. Twists and Wrenches -- Chapter II. The Cylindroid -- Chapter III. Reciprocal Screws -- Chapter IV. Screw Co-ordinates -- Chapter V. General Consideration on the Equilibrium of a Rigid Body -- Chapter VI. The Principal Screws of Inertia -- Chapter VII. The Potential Energy of a Displacement -- Chapter VIII. Harmonic Screws -- Chapter IX. The Dynamics of a Rigid Body which has Freedom of the First Order -- Chapter X. The Dynamics of a Rigid Body which has Freedom of the Second Order -- Chapter XI. The Dynamics of a Rigid Body which has Freedom of the Third Order -- Chapter XII. The Dynamics of a Rigid Body which has Freedom of the Fourth Order -- Chapter XIII. The Dynamics of a Rigid Body which has Freedom of the Fifth Order -- Chapter XIV. The Dynamics of a Rigid Body which has Freedom of the Sixth Order
The theory of screws :, The
Includes index.
Keywords: RIGID BODY